Tendência de HIV Aids entre adultos no Brasil: de 2010 a 2017 - Ceratti, Amanda (Universidade Federal de São Carlos, 2022)
Objective: to analyze the trend of AIDS incidence coefficients and possible points of changes in adults aged 20 to 59 years in Brazil from 2010 to 2017. Method: ecological study of temporal and local series, with data referring to the period from 2010 to 2017, collected at the Department of Informatics of the Unified Health System and on the page from the Brazilian Institute of Geography and Statistics. The cases were divided by regions in Brazil, gender and age group, and to analyze changes in annual incidences by gender and age group, a joinpoint regression model was used. Results: AIDS showed a growing trend among males aged 20 to 29 years in Midwest, Northeast and North regions and remained, for the most part, stationary in the other age groups in both sexes. Conclusion: the need to strengthen Primary Health Care in its role in preventing HIV infection, as well as early detection of seropositive cases and initiation of treatment before reaching AIDS stage; and to expand access to specialized services in other regions beyond of the Southeast and South. Prevention actions and guidelines aimed at the male audience should be stimulated, and also discussed in the school environment, on an ongoing basis, with young people.
HIV Aids trend among adults in Brazil: from 2010 to 2017
Keywords: Incidência; Prevenção e controle; Síndrome da imunodeficiência adquirida; CIENCIAS DA SAUDE::SAUDE COLETIVA::EPIDEMIOLOGIA